2021
DOI: 10.3329/jbcps.v39i4.55944
|View full text |Cite
|
Sign up to set email alerts
|

Comparison among the Role of Different Imaging Techniques in Diagnosis of Malignant Lesions Causing Obstructive Jaundice

Abstract: Introduction: The expanding spectrum of therapeutic options for patients with Obstructive /surgical jaundice makes it necessary for the surgeon to precisely assess the etiology, location, level and extent of disease before operation. Aims were to compare the diagnostic accuracy, sensitivity and specificity of different imaging techniques like ultrasonography (USG), Computed tomography (CT) and Magnetic Resonance Cholangiopancreatography (MRCP) and Endoscopic Retrograde Cholangiopancreatography (ERCP) in evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…This demonstrates that MRCP is an even better diagnostic tool than ERCP. 15 Pramod Chhetri reported an overall diagnostic accuracy of MRCP in benign and malignant causes as 93.98% and 97.6% respectively, which also aligns with our study. 3 A CECT is usually more accurate for determining the type and level of obstruction than an ultrasound scan, however it is less accurate in diagnosing radiolucent calculi.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This demonstrates that MRCP is an even better diagnostic tool than ERCP. 15 Pramod Chhetri reported an overall diagnostic accuracy of MRCP in benign and malignant causes as 93.98% and 97.6% respectively, which also aligns with our study. 3 A CECT is usually more accurate for determining the type and level of obstruction than an ultrasound scan, however it is less accurate in diagnosing radiolucent calculi.…”
Section: Discussionsupporting
confidence: 92%
“…Salma et al in his study reported the diagnostic accuracy of CT for malignant obstructive jaundice as 91.43% and sensitivity as 91.67% respectively which is slightly higher than our study. 15 Mahendra Shrestha has reported diagnostic accuracy and sensitivity of CT scan for benign causes of obstructive jaundice as 90%, 84% and for malignant causes, diagnostic accuracy and sensitivity of CT was 82% and 70%. 17 They determined sensitivity of CT to be slightly less than that of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Expert gastroenterologist and radiologist along with a trained team is needed for the ERCP and procedure is done under sedation or general anesthesia. 5,6 Despite its usefulness, the procedure of ERCP is however related to some unwanted complication which includes sepsis, bleeding, bile leakage, pancreatitis and even a reported rate of mortality up to 1%. 7 A procedure called magnetic resonance cholangiopancreatography (MRCP) introduced in 1991 is now under frequent use for diagnostic purposes in the pathologies related to pancreatic duct and hepatobiliary diseases.…”
Section: Introductionmentioning
confidence: 99%
“…2 The extrahepatic biliary tree can be evaluated with CT, which has the advantages of noninvasiveness, operator independence, and a high technical achievement rate. Nonetheless, CT exposes patients to radiation, and the use of contrast chemicals might cause kidney damage or an allergic reaction.. 3 MRCP is effective for examining the extrahepatic biliary tree. Still, its accuracy suffers when fat planes are few, or the CBD contains little fluid.…”
Section: Introductionmentioning
confidence: 99%